BS ISO 3169. Fine ceramics (advanced ceramics, advanced technical ceramics). Methods for chemical analysis of impurities in aluminium oxide powders using inductively coupled plasma-optical emission spectrometry. (14th March 2022) - British Standards Institution,
No abstract available